THE SOCIAL SIGNIFICANCE OF REGIONAL TOURISM RESOURCE - Anvarova Muhsinakhon Otabek kizi (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Annotation: This scientific article explores the social significance of regional tourism resources and their role in promoting sustainable community development. The study emphasizes how regional tourism contributes to social well-being, cultural preservation, and local participation in tourism management. Using a mixed-method approach, both quantitative surveys and qualitative interviews were conducted to assess the social impacts of tourism in selected regions. The findings reveal that tourism resources not only generate employment and income but also strengthen social cohesion and cultural identity. The research highlights that inclusive and community- based tourism strategies enhance regional development outcomes by ensuring equitable benefit distribution and long-term sustainability. The study concludes with practical recommendations for policymakers to integrate social considerations into regional tourism planning and management.